2017
DOI: 10.19082/6087
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of umbilical artery Doppler and non-stress test in assessment of fetal well-being in gestational diabetes mellitus: A prospective cohort study

Abstract: BackgroundGestational diabetes mellitus (GDM) is one of the most common medical complications of pregnancy and is related to poor perinatal outcomes. Reduction of neonatal complications of GDM is feasible by assessment of fetal well-being. Both fetal Doppler and NST are used for the screening of high-risk pregnancies.ObjectiveWe aimed to compare the non-stress test (NST) and umbilical artery (UA) Doppler assessments for evaluation of the adverse perinatal outcomes in GDM.MethodsWe conducted a prospective cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 21 publications
1
10
0
1
Order By: Relevance
“…reported that abnormal UA Doppler assessment is related with poor neonatal outcome. [ 7 ] In addition Shabani et al . emphasized that MCA PI value increased in GDM patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…reported that abnormal UA Doppler assessment is related with poor neonatal outcome. [ 7 ] In addition Shabani et al . emphasized that MCA PI value increased in GDM patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Niromanesh et al . [ 7 ] emphasized that UA and MCA CDUS changes were effective in predicting poor neonatal outcome in pregnant with GDM. Their method were different, they have evaluated the effect of CDUS changes over pregnancy outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…119,120 In pregnancies complicated by gestational diabetes, 121 or with pre-existing diabetes mellitus without vascular disease, the non-stress test was found to be better than the UA Doppler US at predicting adverse perinatal outcomes. 98,121 Only those complicated with vasculopathy due to diabetes could benefit from periodic UA Doppler US monitoring. 98…”
Section: Umbilical Artery Doppler As a Screening Test In High-risk Pr...mentioning
confidence: 98%
“…117,118 Thus, twin pregnancies benefit from fetal well-being assessment with the UA Doppler US when there is a growth discordance, twin-totwin transfusion syndrome, or IUGR. 119,120 In pregnancies complicated by gestational diabetes, 121 or with pre-existing diabetes mellitus without vascular disease, the non-stress test was found to be better than the UA Doppler US at predicting adverse perinatal outcomes. 98,121 Only those complicated with vasculopathy due to diabetes could benefit from periodic UA Doppler US monitoring.…”
Section: Umbilical Artery Doppler As a Screening Test In High-risk Pr...mentioning
confidence: 98%